The exact location and its relation to cognitive method (risk-caution) of University students - شروق كاظم سلمان (College of Education for Women, 2019)
The present study aimed to identify the exact location and its relation to cognitive method (risk_caution) to university students. The sample consisted of (300) students who were chosen randomly and equally. The study results indicated that students possess an internal exact location and they also use risk cognitive method. The study also indicated that there is a prophesies which is an exact location for others to reach to caution cognitive method. Depending on these results, the study recommended to benefit from the results of the study variables and from the measurement of the exact location and method of cognitive (risk_caution) to identify male and female students and especially by consulting units at colleges to steer those with caution cognitive method in adapting to environmental changes, especially at college, through the development of programs to promote effective behavior.